Disturbance Evolution Behavior of Loess Soil under Triaxial Compression - Yali Xu; Panpan Guo (Advances in Civil Engineering)
This paper presents an investigation into the evolution law of the structural effects of Xi’an loess soil, based on the disturbed state concept. First, a series of consolidated and drained triaxial compression tests were performed on undisturbed and remoulded loess samples prepared at five different moisture contents and tested at four different confining pressures. Second, two disturbance functions with different parameters were proposed to quantify mathematically the structural effects of loess. Finally, the proposed disturbance functions were validated against documented test results by other researchers. The results indicated that the single-parameter disturbance function, with the deformation modulus as its parameter, provides convenience for application but takes no account of the respective contributions of deviatoric stress and mean stress to the disturbance evolution behavior of loess. The double-parameter disturbance function, with the shear and bulk moduli as its parameters, is capable of distinguishing these respective contributions and reflects well the disturbance evolution behavior of loess under various moisture contents and confining pressures. The effects of moisture content and confining pressure on the parameters of the disturbance functions were found to be unsteady. The proposed disturbance functions lay the foundation for establishing a constitutive model for loess accounting for the structural effect.